MENCIPTAKAN KEPUASAN DAN LOYALITAS PELANGGAN MELALUI CITRA DAN SERVICE RECOVERY (Studi pada Restoran Lombok Ijo Semarang) - Ken Sudarti; Iva Atika (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2012)
Customer loyalty is considered by many service providers as an important source of competitive advantage.Enhanced cuatomer loyalty in service firms will lead to greater profitability. The objective of this research is toexamine the effect of image of traditional food and service recovery on the effect on customer satisfaction andcustomer loyalty. Research involved 100 customers. By measuring criterion validity and reliability of image andservice recovery, it found that both of them have a good validity and reliability for measuring the customersatisfaction and cuatomer loyalty. By using path analysis, the result revealed that image, service recovery andcustomer satisfaction have direct significantly effects on customer loyalty. The managerial implication of thisresearch is that management of restaurant should build their image, implement service recovery programconsistanly and create customer satisfaction to miantan their customer.Key words: image , service recovery, satisfaction, loyalty